A micro-level analysis of the effects of aid fragmentation and aid alignment - Hannes Öhler (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
Aid fragmentation and the lack of aid alignment to recipients' policies and processes pose serious challenges to many recipient countries. Consequently, donors have committed themselves to more coordination and alignment in the Paris Declaration (2005) and the Accra Agenda for Action (2008). However, evidence on favourable effects of donors' compliance with these principles is scarce. We contribute to closing this research gap by investigating the effects of aid fragmentation and alignment with the recipient country on infant mortality at the sub-national level within Cambodia. Combining micro panel data on infant mortality and sub-national aid data, our results indicate that the degree of aid fragmentation is of no consequence for development in the health sector. By contrast, common arrangements within programme-based approaches led to positive effects in terms of an improved health situation in the Cambodian provinces. However, the analysis does not point to any beneficial effects of the use of recipient country systems.
Keywords: 330; Wirksamkeit und Evaluierung